Is It Time to Say Farewell to the ISDS System?; Comment on "The Trans-Pacific Partnership: Is It Everything We Feared for Health?" - Raphael Lencucha (Kerman University of Medical Sciences, 2017)
Investor-state dispute settlement (ISDS) continues to plague health-oriented government regulation. This is particularly reflected in recent challenges to tobacco control measures through bilateral investment agreements. There are numerous reform proposals circulating within the public health community. However, I suggest that perhaps it is time for the community to explore a stronger position on ISDS. I draw from mounting evidence on the problematic uses of the ISDS to explore the proposition that ISDS is no longer justified. I tackle the normative question of shouldthe ISDS system persist and point out that the ISDS system is not justifiable from a development perspective and because of its nefarious use, is of no added value to a system that could rely on domestic courts.